Formal and informal institutions and the economic development in Latin America - Paula Regina de Jesus Pinsetta Pavarina; Daltro Cella (European Regional Science Association (ERSA), 2015)
This paper aims to collaborate with the discussion about the factors that try to explain the economic behavior in Latin America countries, considering the importance of some attributes related to social capital (ie interpersonal trust, which leads to association and civic commitment, performing what Putnam (1993) considers a 'civic community') pari passu the institutional behavior, ie the ?rules of the game in a society? (North 1990). These two dimensions attempt to explain the behavior of agents facing the rational economic decision of cooperate or not. It can be stated that this decision depends on two factors: (1) the expected behavior of other agents ('I cooperate if the other will also cooperate') and (2) the existence of standards, patterns or rules that hinder or prevent opportunism (in order to avoid that cooperation seems a 'fool?s choice'). The more generalized trust is, it is expected that there will be more cooperation. Furthermore strong institutions that can enforce pre-established rules reduce the uncertainty and insecurity of the decision-making process. The key question when these two dimensions are considered at the same time is if they are complementary or substitute to each other in Latin America context. In other words, it tries to understanding the relationship between formal and informal 'rules of the game' as well as high levels of social capital to the economic behavior and economic actions. Then this study assesses the contribution of these two elements to the economic performance of Latin America, considering data provided by large international databases such as Latinobarometro, World Values Survey, Index of Economic Freedom, Worldwide Governance Indicators, International Country Risk Guide, and Polity IV. Theoretically, it is easy to display the relationships that can be established between these concepts but in practice, there is great methodological difficulty to quantify them. Thus, several indicators or proxies are selected among all the possible variables that exist in these databases. Social capital can be represented by very subjective elements such as trust, values and assimilation of social norms. The same difficulty occurs when it is considered the role of institutions; since it is difficult to evaluate the effective contribution of formal institutions to economic performance. The simple existence of institutions, understood as formal 'rules of the game', does not guarantee that they are fulfilling their intended functions.
Keywords: A13; O17; 330; institutions; economic development; latin america